Prevalence of limbal stem cell deficiency at an academic referral center over a two-year period - Goldberg, Jason S.; Fraser, Daniel J.; Hou, Joshua H. (Frontiers in Ophthalmology, 2024)
AimTo evaluate the prevalence and clinical characteristics of limbal stem cell deficiency (LSCD) in the setting of a tertiary referral cornea practice at an academic center.Patient and methodsA retrospective chart review was performed to identify all unique medical record numbers (MRNs) presenting to a single cornea specialist (JHH) at the University of Minnesota during calendar years 2019 and 2020. Records were queried and confirmed for a diagnosis of LSCD. Clinical characteristics of identified patients, including demographics, etiology of LSCD, severity of LSCD, treatment, and best corrected visual acuity (BCVA) at final follow-up, were documented.ResultsIn total 1436 unique MRNs were identified over the study period. There were 61 individuals (91 eyes) diagnosed with LSCD, resulting in a prevalence of 4.25% (95% CI, 3.33-5.42). Of 91 eyes, 60 eyes were bilateral (65.9%). Among all eyes, ocular surface burns were the most common etiology (18.7%) followed by iatrogenic or medicamentosa (15.4%). There were 51 eyes (56.0%) that underwent some form of transplantation. The median BCVA at final follow-up was Snellen 20/80 (range 20/20 to no light perception).ConclusionsThe prevalence of LSCD found at a cornea subspecialty tertiary referral center in our study was much higher than previously reported prevalence rates. This may reflect referral bias and potential underdiagnosis of LSCD in practices outside of subspecialty referral centers. The high prevalence rate in our study also suggests that LSCD patients are concentrated in subspecialty referral practices, with many having high morbidity disease. This constitutes a major health burden for these practices.